Uranium fluoride micromaterials: a new frontier in nuclear engineering - Jang, Harry; Poineau, Frederic (Frontiers in Nuclear Engineering, 2025)
This perspective explores recent advancements in the synthesis and application of uranium fluoride micromaterials, emphasizing their role in the nuclear industry. Uranium micromaterials, including oxides, fluorides, and carbides, are crucial for applications ranging from high-temperature gas-cooled reactors to nuclear forensics and medical isotope production. The perspective highlights a novel chemical transformation process for synthesizing uranium fluoride micromaterials, in which uranium oxides are fluorinated in an autoclave using HF gas (generated from the decomposition of silver bifluoride) or ammonium bifluoride while preserving their original morphologies. This transformation produces various uranium fluoride microstructures, including UF4, UO2F2, and (NH4)3UO2F5, in the form of microrods, microplates, and microspheres. The perspective discusses challenges in maintaining controlled morphologies during fluorination and explores future directions, such as the synthesis of actinide fluoride micromaterials and the development of uranium chloride and other uranium compounds. The continued advancement of these materials holds significant potential for innovations in nuclear fuel cycles, actinide material chemistry, and nuclear forensics.